West of the wall: Reflections of lock down in delivery during COVID-19 - Heckenberg, Robyn; Karia, Ajay; Corunna, Vanessa; Goerke, Veronica; Oriti, Sam; Owen, Julie; Shahid, Shaouli; Shaw, Robert; Zegarac, Marko (informit, 2020)
This is a different way of us sharing our thoughts in the way we formulate and "write-up" our strategies regarding COVID-19, incorporating an Indigenous way of sharing. A group of academic staff in the Centre for Aboriginal Studies (CAS), Curtin University, Perth, decided to share their reflections on the COVID-19 lockdown and the ensuing challenges inherent in being in teaching and learning in an Indigenous space through COVID-19 times. The manner of our knowledge sharing is simplified because each writer/speaker takes up the message stick and has their conversation (yarn) about their experiences: this includes an introduction within the text of who the speaker is, but at times does digress, as "yarning" may. Then the Message Stick goes to the next speaker to continue the conversation till we get to the finish of our story. This is our written version of a "yarning circle", which is a way of sharing narratives that is very popular in this corner of South Western Australia.